Behavioral Simulation of ISO 18000-6 Type-C Class 1 Gen2 Protocol for RFID UHF Transponder and its Application as Anti-collision Protocol in Interference Case - Saadi, Hadjer; Rnnane, Ahmed; Touhami, Rachida; C.E. Yagoub, Mustapha (International Journal of Engineering and Technology, 2018)
In RFID systems, the Transponder Protocol usually uses the standard ISO 18000-6 Type-C Class 1 Generation 2, originally developed to communicate with the reader. Since a typical RFID system could be used in a myriad of tasks from product identification to environmental sensing, behavioral software functionality and hardware cost constraints are extremely constricted, principally due to their Â¶standardâ€™s requirements.Â¶ Thus, in this paper, an advanced behavioral simulation of the Tag ID layer of ISO 18000-6 Type-C protocol is proposed with all its states, commands and functionality, a crucial step toward effective design and test. The approach was then successfully applied to collision issues in interference case.Â Â